THE NOTARY IN AUTHORITY’S MAKING OF HYPOTHEEK - Denny Suwondo; Siti Nurdiyah Fauza Tuanaya (Jurnal Pembaharuan Hukum, 2018)
Pursuant  to  Article  15  paragraph  (2)  letter  (f)  of   Act  No.   2  of  2014   concerning  Notary,  the   Notary  as  Public  Official  obtain  Attribution  of  powers  in  a  deed  relating  to  land,  including  the   deed  of  the  Power  of  Attorney  Imposing  Mortgage.  This  study  aims  to  know  and  understand  the   authority  of  the  deed  Notary  Power  of  Attorn ey  Imposing  Mortgage.  The  method  used  socio - juridical,  which  inductively  began  an  analysis  of  the  legislation  governing  the  Notary  office  and   encumbrance  on  land  and  objects  relating  to  the  ground.  Research  shows  that  the  authorities  in   deed  Notary  Power  o f  Attorney  Imposing  Mortgage  is  based  on  Article  15  (1)  of   Act  No.   4  of   1996  on  Mortgage  of  Land  and  Their  Bodies  Relating  to  dust  and  Article  15  (2)  f  of   Act  No.   2  of   2014  on  the  Amendment  of  Act  30  of  2004  on  Notary.  That  in  practice  the  National  Land   Ag ency  of  the  Republic  of  Indonesia  only  receive  the  Power  of  Attorney  Imposing  Mortgage  in   the  form  of  deed  Land  Deed  Officer.